EVALUATION OF EXISTING HAULING ROAD GEOMETRY TO INCREASE NICKEL LATERITE PRODUCTION AT PT. PUTRA MEKONGGA SEJAHTERA - Aswar, Aidil; Salu, Sahrul Poalahi; Arif, Arif (Fakultas Teknik Universitas Khairun, 2024)
PT Putra Mekongga Sejahtera is a nickel laterite mining company located in Pomalaa District, Kolaka Regency, Southeast Sulawesi Province. In a mining activity, many factors affect the aspects of production achievement, one of which is the haul road. Haul roads make a major contribution to smooth transportation operations if the road geometry is in accordance with the dimensions of the conveyance used, then the production target of 80,000 tons / month can be achieved. The current field conditions in terms of road geometry are considered unrepresentative for the movement of hauling equipment and can interfere with mining activities. Based on actual haul road geometric measurements between 5.41-16.98 meters while the theoretical road width for straight roads is 8.72 meters. The actual bend road width ranges from 5.50-15.10 meters while the theoretical bend road width is 14.32 meters. The actual road slope ranges from 0.35% to 17.30% while the maximum road slope is 12%. After evaluation, there are 4 straight road segments that need to be increased in width, namely segments AB, BC, CD and DE and 5 segments of bend road width, namely segments AB, BC, CD, DE and EF, as well as grade reduction in segments AB, BC, DE and EF. Hino FM 260 JD dump truck production before road geometry improvement is 3029 tons/day or 78761.75 tons/month. Hino FM 260 JD dump truck production after ideal road geometry improvement is 3143 tons/day or 81724.38 tons/month.Â